1981
DOI: 10.1007/bf00435849
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking different doses of nicotine on human aggressive behavior

Abstract: A new methodology was employed to study the effects of drugs on human aggressive behavior in a laboratory situation. The effects of not smoking, smoking a low nicotine dose (0.42 mg/cigarette), and smoking a high nicotine dose (2.19 mg/cigarette) on human nonaggressive and aggressive responding was determined. A nonaggressive response, which resulted in the accumulation of money, was continuously available to the subject. Two different aggressive responses were also available: the ostensible subtraction of mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
0
15

Year Published

1983
1983
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(119 citation statements)
references
References 21 publications
5
99
0
15
Order By: Relevance
“…Um modelo psicofarmacológico experimental para o estudo de agressão em humanos, denominado Point Subtraction Aggression Paradigm (PSAP) (Cherek, 1981), apresenta, entre suas fundamentações empíricas, o modelo de "painaggression" (Miczek, 1987) e é relativamente bem-aceito na comunidade científica como um índice de mensuração em laboratório da agressividade humana (Geniole, MacDonell, & McCormick, no prelo).…”
Section: Análise Do Comportamento "Pain-aggression" E Algumas Repercunclassified
“…Um modelo psicofarmacológico experimental para o estudo de agressão em humanos, denominado Point Subtraction Aggression Paradigm (PSAP) (Cherek, 1981), apresenta, entre suas fundamentações empíricas, o modelo de "painaggression" (Miczek, 1987) e é relativamente bem-aceito na comunidade científica como um índice de mensuração em laboratório da agressividade humana (Geniole, MacDonell, & McCormick, no prelo).…”
Section: Análise Do Comportamento "Pain-aggression" E Algumas Repercunclassified
“…1986;Grunberg, Winders, & Wewers, 1991;Klesges & Klesges, 1988;Klesges, Meyers, Klesges, & La Vasque, 1989). Other smokers indicate that smoking alleviates boredom (Parrott, 1995), reduces anxiety (Pomerleau, Turk, & Fertig, 1984;Gilbert, Robinson, Chamberlin, & Spielberger, 1989;Kassel & Shiffman, 1997), tempers hostility (Cherek, 1981;Cherek, Bennett, & Grabowski, 1991), and generally assists in mood regulation (Parrott, 1995). Further, some smokers report that smoking enhances 6 including environmental as well as psychological factors.…”
Section: Major Effects Of Nicotine That Contribute To Self-administramentioning
confidence: 99%
“…In fact, literature II relevant to biologically-mediated individual differences in nicotine's effects indicates that nicotine is the agent responsible for the major reported effects of smoking. Specifically, in empirical studies, nicotine administration decreased body weight in humans and rats (Grunberg, 1982;Winders & Grunberg, 1989), decreased aggression in humans (Cherek, 1981;Cherek et aI., 1991) and in rats (Silvennan, 1971;ScheufeJe, 1997), and altered biochemical and behavioral responses to stress in rats (Benwell & Balfour, 1982;Cam & Bassett, 1983;1984;Sharp, Beyer, Levine, Morley, & McAllen. 1987;Peck, Dilsaver, & McGee, 1991;Acri, 1992Acri, , 1994Takada, Thara, Vrano, & Takada, 1995) and in humans (MacDougall, Musante, Castillo, & Acevedo, 1988;Gilbert, Robinson, Chamberlin, & Spielberger, 1989;Pomerleau & Pomerleau, 1990;Levin, Rose, Behm, & Caskey, 1991;Smits, Temme, & Thien, 1993).…”
Section: ) Effects Of Nicotinementioning
confidence: 99%
“…In turn, these learned behaviors are generalized to nonsporting contexts and used to obtain external rewards. To illustrate this idea, Huang, Cherek, and Lane (1999) used the Point Subtraction Aggression Paradigm (PSAP; Cherek, 1981) and compared male contact, and noncontact, athletes. Interestingly, it was found that contact athletes were more sensitive to provocation and significantly more likely to respond aggressively by stealing points from their opponents compared to noncontact athletes.…”
Section: Introductionmentioning
confidence: 99%